Hybrid e-learning tool TransLearning: video storytelling to foster vicarious learning within multi-stakeholder collaboration networks. Issue 4 (3rd July 2016) - van der Meij, Marjoleine G.; Kupper, Frank; Beers, Pieter J.; Broerse, Jacqueline E. W.
Abstract: E-learning and storytelling approaches can support informal vicarious learning within geographically widely distributed multi-stakeholder collaboration networks. This case study evaluates hybrid e-learning and video-storytelling approach 'TransLearning' by investigation into how its storytelling e-tool supported informal vicarious learning, while it was applied in multi-stakeholder collaborations called 'Regional Ateliers'. TransLearning was meant to supplement learning within RAs about running rural sustainable innovation projects. The e-tools' video-stories were thematically coded for content analysis. Stakeholder workshops in which the e-tool was used, as well as gathered user experiences, were transcribed, analysed inductively and juxtaposed. Findings indicate that stakeholders vicariously learned by (1) creative association and (2) collaborative creation of new stories, based on watching individual or multiple videos, respectively. However, the e-tool's learning content seemed rife with conceptual knowledge, indicating an absence of concrete experiences that are essential for rich(er) vicarious learning. Storytelling e-tools developed for vicarious learning in novice collaborations may inherently encounter this. To conclude, hybrid storytelling approaches like TransLearning seem to support informal vicarious learning best if they employ (1) processes in which learners actively co-create content (selection of topics and storytellers), (2) extensive storyboarding (3) and learning facilitators that encourage learners to collaboratively compare videos and think associatively.